Chapter 1 Disrupted development in the Congo - Radley, Ben (Oxford University Press, 2023)
This introductory chapter sets out the book’s aims and contributions, outlines its main lines of argument, and details the theoretical foundations underpinning the African Mining Consensus, which holds that transnational mining corporations are best placed to drive structurally transformative processes of mining-based development on the continent. It then moves on to document how, in establishing this Consensus position, proponents have tended to misrepresent or disregard some of the classic critiques mounted by a group of pioneering early development economists. These critiques focused on the specific challenges and constraints faced by income-poor peripheral countries seeking development through deeper integration with the global capitalist economy. Returning to these earlier critiques provides helpful lenses with which to explore, with some adaptation, several axes of tension within the ongoing process of foreign corporate-led mining industrialization in low-income African countries that are overlooked by the absent or simplistic representation of these critiques by Consensus proponents.